Pemetaan Potensi Desa Berbasis Asset Based Community Development di Desa Kotabatu, Pubian, Lampung Tengah - Yulianto; Fahmi, Teuku; D. Meilinda, Selvi; A. Hidayati, Dewi; Inayah, Astiwi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
The purpose of this community service activity was to increase the knowledge and experience of local communities at village potential mapping based on Asset Based Community Development in Kotabatu Village. The activities carried out are in the form of focus group discussion (FGD), training that accompanied by assistance in the context of mapping of village potential and increasing the institutional capacity of community groups, namely: Community Forestry Group and Tourism Awareness Group. The methods used in this activity included: the cognitive aspect enhancement stage, the mentoring and empowerment stage, and the advocacy stage. In particular, this community service activity has led to several objectives, including: building a commitment among village officials to focus on village development of the three potential Kotabatu Village has had, including (1) optimizing the potential of natural resources, (2) potential agricultural products, and (3) tourism potential. ===== Tujuan pelaksanaan kegiatan pengabdian ini ialah meningkatkan pengetahuan dan pengalaman masyarakat lokal dalam memetakan potensi desa berbasiskan asset based community development di Desa Kotabatu, Kec. Pubian, Kab. Lampung Tengah. Kegiatan yang dilakukan berbentuk forum group discussion (FGD), pelatihan, dan dibarengi dengan pendampingan dalam rangka pemetaan (eksplorasi) potensi desa, serta peningkatan kapasitas kelembagaan kelompok masyarakat, yakni Kelompok Hutan Kemasyarakatan-HKm dan Kelompok Sadar Wisata (Pokdarwis). Metode yang digunakan dalam kegiatan ini di antaranya adalah tahap peningkatan aspek kognitif, tahap pendampingan dan pemberdayaan, serta tahap advokasi. Secara khusus, kegiatan pengabdian ini telah mengarah pada beberapa capaian tujuan, di antaranya, yakni terbangunnya komitmen di antara aparatur desa untuk memfokuskan pengembangan desa pada tiga potensi yang dimiliki oleh Desa Kotabatu, di antaranya, yakni (1) optimalisasi potensi SDA, (2) potensi hasil bumi, dan (3) potensi pariwisata.